199k views
3 votes
Plz hellppppp (6h + 8) - (3h + 2) = 15

User Toji
by
5.6k points

2 Answers

6 votes

(6h + 8) - (3h + 2) = 15

Let's distribute the - to 3h + 2

6h + 8 - 3h - 2 = 15

Combine like terms

3h + 6 = 15

Subtract 6 from both sides

3h = 9

Divide both sides by 3

h = 3

User Jacob Bruinsma
by
5.2k points
1 vote

Answer:

h = 3

Explanation:

Step 1: Write out equation

(6h + 8) - (3h + 2) = 15

Step 2: Distribute negative

6h + 8 - 3h - 2 = 15

Step 3: Combine like terms

3h + 6 = 15

Step 4: Subtract 6 on both sides

3h = 9

Step 5: Divide both sides by 3

h = 3

Step 6: Check Step

(6(3) + 8) - (3(3) + 2) = 15

(18 + 8) - (9 + 2) = 15

26 - 11 = 15

15 = 15

User Serafeim
by
5.0k points